EARTH 2.0 - Panayides, Angelos (My University, 2023)
Created in response to an invitation to participate in the 5th Emirates International Poster Festival (EIPF), this poster aligns with the festival’s central theme, ‘Design for Climate Change.’ his edition of EIPF coincides with the UAE’s hosting of the 28th Conference of the Parties to the UN Framework Convention on Climate Change (COP28) in Expo City Dubai, scheduled for November 2023.
Keywords: international, poster, exhibition